Iklim Keselamatan Kerja dan Program K3 di Proyek Pembangunan Gedung X Surabaya - Ro’is, Rachmy Rosyida; Wahyudiono, Yustinus Denny Ardyanto; Bahar, Ria Rezki Ramadhani (FORIKES, 2022)
One of the factors that can influence workers' compliance with the Occupational Safety and Health program is the safety climate, namely workers' perceptions of managerial commitment related to work safety. Occupational safety climate includes 7 dimensions namely commitment and capability of safety management; empowering safety management; fairness of safety management; workers' commitment to work safety; worker safety priority and intolerance of hazard risks; learning, communication, and innovation; and confidence in the effectiveness of the safety system. So research is needed that aims to determine the conditions of the safety climate and occupational health and safety programs in the X building construction project in Surabaya. This descriptive study involved 30 finishing foremen selected by accidental sampling technique. Data was collected by filling out the NOSACQ-50 questionnaire to workers and interviewing HSE staff regarding the Occupational Health and Safety program at the X Building Construction Project in Surabaya. The results of the analysis showed that there were 4 dimensions that fall into the sufficient category and need improvement, 2 dimensions were in the good category and need a little improvement, and 1 dimension was in the less category and needs a big improvement. Efforts to improve can be made related to building worker participation, outreach related to safety, and program evaluation.Keywords: safety climate; management; occupational health and safety ABSTRAK Salah satu faktor yang dapat mempengaruhi kepatuhan pekerja terhadap program Keselamatan dan Kesehatan Kerja adalah iklim keselamatan, yaitu persepsi pekerja terhadap komitmen manajerial terkait keselamatan kerja. Iklim keselamatan kerja mencakup 7 dimensi yakni komitmen dan kemampuan manajemen keselamatan; pemberdayaan manajemen keselamatan; keadilan manajemen keselamatan; komitmen pekerja tehadap keselamatan kerja; prioritas keselamatan pekerja dan tidak ditoleranisnya risiko bahaya; pembelajaran, komunikasi, dan inovasi; serta kepercayaan terhadap keefektifan sistem keselamatan kerja. Maka diperlukan penelitian yang bertujuan untuk mengetahui kondisi iklim keselamatan dan program kesehatan dan keselamatan kerja di proyek pembangunan gedung X di Surabaya. Studi deskriptif ini melibatkan 30 pekerja mandor finishing yang dipilih dengan teknik accidental sampling. Data dikumpulkan melalui pengisian kuesioner NOSACQ-50 kepada pekerja dan wawancara kepada staff HSE terkait program Kesehatan dan Keselamatan Kerja di Proyek Pembangunan Gedung X di Surabaya. Hasil analisis menunjukkan bahwa terdapat 4 dimensi yang masuk ke dalam kategori cukup dan butuh peningkatan, 2 dimensi kategori baik dan butuh sedikit peningkatan, serta 1 dimensi kategori kurang dan butuh peningkatan yang besar. Upaya peningkatan dapat dilakukan terkait dengan membangun partisipasi pekerja, sosialisasi terkait keselamatan, dan evaluasi program.Kata kunci: iklim keselamatan; manajemen; keselamatan dan kesehatan kerja